Original Articles: Translational Oncology - Pooled Analysis of the Prognostic and Predictive Value of KRAS Mutation Status and Mutation Subtype in Patients with Non–Small Cell Lung Cancer Treated with Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors. Issue 3 (March 2016) - Zer, Alona; Ding, Keyue; Lee, Siow Ming; Goss, Glenwood D.; Seymour, Lesley; Ellis, Peter M.; Hackshaw, Allan; Bradbury, Penelope A.; Han, Lei; O'Callaghan, Christopher J.; Tsao, Ming‐Sound; Shepherd, Frances A.
ABSTRACT : Objectives: : This pooled analysis of four trials of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) versus placebo was conducted to clarify the prognostic and predictive roles of Kirsten rat sarcoma viral oncogene homolog ( KRAS ) mutations (MUTs) and to explore the importance of MUT subtype. Methods: : Data were pooled from four trials of EGFR TKIs versus placebo (National Cancer Institute of Canada Clinical Trials Group [NCIC CTG] trial BR.21, TOPICAL, NCIC CTG trial BR.26, and NCIC CTG trial BR.19). Analyses of the combined data were performed to determine relationships of MUT status/subtype to response and survival end points. Results: : KRAS status was known for 1362 of 2624 patients (785 receiving EGFR TKIs and 577 receiving placebo); 275 (20%) had KRAS MUTs (248 at codon 12; 15 at codon 13; 12 at other codons). In the placebo arms there was no difference in overall survival (OS) for patients with KRAS MUTs or wild‐type tumors (hazard ratio [HR] = 1.04, confidence interval [CI]: 0.81–1.33 for univariable analysis and HR = 1.09, CI: 0.85–1.41 for multivariable analysis). Patients with guanine‐to‐thymidine transversion MUTs had longer OS than did those with guanine‐to‐adenine transition MUTs or guanine‐to‐cytosine transversion MUTs (median OS 6.3, 1.8, and 3.9 months, respectively, p = 0.01). Patients with KRAS MUT tumors derived no benefit from EGFR TKIs (OS HR = 1.13, CI: 0.85–1.51; progression‐free survival HR = 1.02, CI: 0.76–1.36). The interaction between KRAS status and EGFR TKI effect was significant for progression‐free survival ( p = 0.04) but not for OS ( p = 0.17). For patients with G12V MUTs, EGFR TKI treatment was harmful (OS HR = 1.96, CI: 1.03–3.70, p = 0.04), whereas guanine‐to‐adenine transition MUTs were associated with an OS benefit from EGFR TKIs (HR = 0.49, CI: 0.24–1.00, p = 0.05). Conclusions: : Overall, KRAS MUT is neither prognostic nor predictive of benefit from EGFR TKIs. However, it appears that KRAS MUT subtypes are not homogeneous in terms of their prognostic and predictive effects. These observations require prospective validation.